An unusual case of osteoarthritis?. Issue 8 (21st August 2021) - Teixeira, Mariana; Ricardo Pires, Joana; Ferreira, Filipa Coroado; Rabadão, Tiago; Aveiro, Marcelo; Neves, Nuno; Neves, Clarinda
Abstract: Forestier disease is a condition characterized by calcification and ossification of ligaments and entheses particularly affecting axial skeleton. Diagnosis is difficult and mandates a high suspicion level, but unexpensive and accessible examinations like a simple radiography might provide useful diagnostic clues in these challenging clinical scenarios and improve clinical assistance. Abstract : Forestier disease is a condition characterized by calcification and ossification of ligaments and entheses particularly affecting axial skeleton. Diagnosis is difficult and mandates a high suspicion level, but unexpensive and accessible examinations like a simple radiography might provide useful diagnostic clues in these challenging clinical scenarios and improve clinical assistance.